Evaluating Genders’ Mental Model Patterns for User Interface Design: Mobile Shopping Apps. - Aslina Baharum; Noor Fzlinda Fabeil; Nur Shahida Ab Fatah; Sharifah Milda Amirul; Nurul Hidayah Mat Zain; Rozita Ismail (2018)
Mobile applications (apps) development has experienced unprecedented growth, particularly in smartphone platforms. However, some mobile App. have been seen declining in popularity due to the unattractive user interface and bad user interaction with the users. This study adopted user's mental model pattern is crucial in human computer interaction. A guideline has been proposed for user interface design of mobile shopping App. based on female and male mental model patterns. The proposed guideline has been used in this research to redesign an existing popular mobile shopping App., Lazada and user interaction with the adapted user interface has been evaluated through simulation tool, namely AZ Screen Recorder. This research demonstrates an adapted interface design with guideline of user's mental model pattern is more efficient compared to interface design without adapted guideline.